Reversão anaglífica baseada em método rápido - Machado, Felipe Carneiro; Goularte, Rudinei (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
3D formats are still relevant due to their ability to convey depth through stereoscopic techniques. Among these, the anaglyph method stands out for its simplicity and low cost, encoding stereo pairs into a single image. Despite its advantages in compression and transmission, anaglyph encoding discards significant information, making its reversion complex. Reversing anaglyphs enables legacy content recovery and broader compatibility with various stereoscopic visualization methods. This work proposes an efficient approach to anaglyph reversion by exploring Block Matching algorithm, commonly used in video coding. Unlike traditional methods relying on pixel descriptors and global optimizations—often computationally expensive—our technique aims to handle radiometric differences between stereo views while maintaining high image quality and improved performance. Experimental results demonstrate the potential of this method as an alternative to existing solutions.